Rancang Bangun Sistem Informasi Pendaftaran dan Pengelolaan Data Menggunakan Metode Waterfall pada Percik Playground and Learning - Ferdilan Romansyah; Firman Aziz Saputra; Rika Julia Dewi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Percik Playground and Learning is an early childhood education institution that implements a play based learning approach in its educational activities. The institution currently faces challenges because the student registration and data management processes are still carried out manually. As a result, data are not well organized, information retrieval is time-consuming, and communication with parents is not conducted effectively. This study aims to design and develop a web-based registration and data management information system using the Waterfall software development method. The research methodology includes observation, interviews, literature review, and system development based on the Waterfall approach. The results of this study are a web-based information system design that supports student registration, student data management, class management, learning schedules, and activity information that can be accessed by administrators and parents. The proposed system is expected to improve the efficiency and effectiveness of data management while facilitating the dissemination of information at Percik Playground and Learning.